Uncertainty analysis for estimation of landfill methane emissions - SZEMESOVÁ, Janka; GERA, Martin (Contributions to Geophysics and Geodesy, 2021)
For better estimation of emissions the IPCC Guidelines are followed and the country specific methodology for the waste sector is developed. The database of the Center of Waste Service and Environmental Management in Bratislava has been used as a source of input data. GHG emissions from the solid waste disposal sites are the key source and the actual emission factors are estimated with a high uncertainty level. The Emission uncertainty calculation of landfill by using the more sophisticated Tier 2 – Monte Carlo method is evaluated in this article. For this reasons the software package, which works with probabilistic distribution and their combination, was developed. The results and computational methodology of methane emissions from solid waste disposal sites are presented.